Milton’s Shakespeare: Imitation and Originality - Stevens, Paul (Renaissance and Reformation / Renaissance et Réforme, 2022)
Encouraged by the recent renewal of interest in the relationship between Milton and Shakespeare, this essay focuses on that relationship in the light of the tension between the literalism of sola scriptura in reformed religion, on the one hand, and the countervailing insistence on imitation as the route to originality and individual agency in the studia humanitatis, on the other. This tension is central to all Milton’s thinking; at its core is the question, “How are we to reconcile God’s freedom with our own?” While God’s freedom is absolute, we are nothing more than puppets “in the motions” unless we find a way to define the contingency of our own. Milton is intoxicated with the majesty of God’s freedom but equally haunted by the memory of our own original freedom: “No man who knows ought, can be so stupid [as] to deny that all men naturally were borne free, being the image and likeness of God himself.” By concentrating on Milton’s representation of Shakespeare in his “Epitaph” on Shakespeare (1632) and Eikonoklastes (1649), my argument is that not only is Milton’s engagement with Shakespeare ongoing but that it allows us peculiar insight into the poet’s conflicted desire both to create enhanced space for human agency and to critique its overestimation, especially in the idealization of political virtù.